Output Effects of a Changing Composition of Industry 1947-1965 - Shaw, Lawrence H.; Arden, Robert S. (The Review of Economics and Statistics, 1968)
Aggregate measures of output per man or output per man-hour, such as those regularly published in the Economic Report of the President, are frequently used as indicators of changes in aggregate productivity. These measures reflect both changes in output per man (or man-hour) in individual sectors of the economy and sectoral shifts in the composition of output. While this dual nature has been long recognized, it has not received sufficient attention.' The causative forces for productivity growth in a particular sector are entirely different from those accounting for shifts among sectors.2 Table 1 presents a measure of composition effects which allows for the separate analysis of sectoral productivity change and sectoral shifts. The measure which is used here has been discussed at length elsewhere.3 Briefly the procedure used derives from the following propositions: (1) Aggregate measures of output per man are derived by dividing aggregate output by an aggregate input measure, be it the total number of men or man-hours. (2) The output per man measure thus derived is an implicitly weighted average of output per man in all sectors of the economy, number of men being used as weights.4 As a result the aggregate input measure is equally weighted while the aggregate productivity measure is differentially weighted. (3) Because there is no justification for differentially weighting productivity that would not apply to the input measure, it is less arbitrary to isolate the weighting factor as a third component of output, which might be termed the effect of composition.5 Consistency is thus afforded in the treatment of aggregate input and productivity measures, and greater emphasis is placed on sectoral shifts as a source of growth in output.